The Influence Of Mixed Beverage Product Quality On Customer Satisfaction At D'lounge Aston Makassar Hotel - Baskoro, Dimas Aryo; Anggoro, Damas Aryo (Universitas Negeri Padang, 2022)
D'lounge is a public bar that has a concept in the form of a bar and restaurant. This study used a simple random sampling method with a sample of 92 respondents. Data analysis used descriptive statistical methods, validity test, reliability test, normality test, heteskedastisity test, coefficient of determination test (R2) and hypothesis test. The research was conducted in January 2022 - June 2022. Based on the results of the data above the results of the normality test with Kolmogorov – Smirnov produce an Asymp value. Sig. a sig of 0.062 which is greater than 0.05 so it can be concluded that the research data is normally distributed. it is known that the significance value of the Product Quality variable (X) is 0.916. It can be seen that the significance value is greater than 0.05 (0.916 > 0.05). It can be concluded from the processing of the heteroscedasticity test above that heteroscedasticity does not occur while it is known that the calculated F value = 1,685 with a significance level of 0.000 <0.05, so the regression model can be used to predict the participation variable or in other words there is an influence of the Quality variable (X) on the variable Consumer Satisfaction (Y). The results of the F test in table 4.36 obtained Fcount of 66.155 > Ftable 3.949 with a sig value of 0.000 <0.05, so that Ha is accepted, meaning that there is a simultaneous effect of the quality of beverage products on consumer satisfaction which is significant and the regression model can be used. Significance value 0.000 <0.05. So it can be concluded that Ha is accepted, namely the influence of Mixed Drink Product Quality on consumer satisfaction and H0 is rejected. So that the lowest Mean value is 3.58% on the indicator of diversity of mixed drink variants so that D'lounge management is expected to add variants or types of mixed drink menus to attract buyers so as to create consumer satisfaction.